Finding Psychological Well-Being: The Role of Parental Gratitude in Raising Children with Autism at SLB X Samarinda - Purbasetya, Abdha; Umaroh, Siti Khumaidatul; Mariska, Silvia Eka (Jurnal Psikologi Terapan, 2024)
The birth of a child with developmental disorders, such as autism, presents a significant challenge for parents. This study aims to examine the effect of gratitude on psychological well-being of parents with autistic children. Psychological well-being refers to aspects of self-acceptance, positive relationships with others, life purpose, personal growth, and autonomy. The study used a quantitative approach with a correlational design, with a sample of 61 parents of autistic children from SLB X Samarinda City. Data were collected through questionnaires consisting of two scales: Psychological Well-being and Gratitude, analyzed using simple regression. The results showed that gratitude significantly influenced psychological well-being, explaining 38.1% of the variability in psychological well-being. The higher the level of gratitude, the better the psychological well-being of the parents. These findings support the theory that gratitude plays a crucial role in enhancing psychological well-being. The study suggests that gratitude-based interventions be applied to improve the psychological well-being of parents with autistic children, and as a foundation for developing more effective psychological support programs.